Improved Survival and Quality of Life Through an Integrative, Multidisciplinary Oncological Approach: Pathophysiological Analysis of Four Clinical Cancer Cases and Review of the Literature - Berretta, M.; Morra, A.; Taibi, R.; Monari, F.; Maurea, N.; Ippolito, M.; Tirelli, U.; Fiorica, F.; Montella, L.; Facchini, G.; Quagliariello, V.; Montopoli, M. (Frontiers in Pharmacology, 2022)
Objectives: According to the National Cancer Institute, the integrative medicine (IM) approach to medical care combines standard medicine with complementary and alternative medicine practices that have proved safe and effective. Methods: We describe the clinical cases of four patients with malignant pleural mesothelioma (MPM), diffuse malignant peritoneal mesothelioma (DMPM), intrahepatic cholangiocarcinoma, and breast cancer (BC) who received supportive treatment (ST) according to an IM approach after the failure of standard cancer treatments or the appearance of serious adverse events caused by antiblastic chemotherapy. The critical role of complementary drugs in reducing the side effects of cancer treatments and normalizing the white cell count is especially apparent in the case of the patient with metastatic BC, who experienced prolonged neutropenia. Results: The IM approach was well-tolerated and had no adverse side effects. It improved the quality of life (QoL) of all patients and in two cases extended overall survival. Conclusion: The extended clinical and instrumental response to IM of the patients with malignant mesothelioma and the improved health-related QoL and good tolerance of the ST demonstrated in all cases support the value of this approach in patients whose cancer therapies have failed but who show a good performance status. Our data require confirmation in a well-designed prospective clinical trial.